Meningkatkan Kompetensi Guru Kelas dalam Proses Pembelajaran Melalui Supervisi Akademik di SD Negeri 4 Mataram - Jamilan, Jamilan (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2017)
The purpose of this study is to determine the effectiveness of the implementation of academic supervision in an effort to improve the competence of classroom teachers in learning in the classroom, the benefits for the principal is to know the improvement of teachers in the learning process.This research was conducted for two cycles, each cycle activity there are four stages of planning, implementation, observation, and reflection. The indicators of success in this study are; 1) the results of principal observation and teacher observation during the mentoring process have obtained the average score> 4.0, 2) the result of the average teacher in the learning process reaches> 85% with the average value> 70.00 (good category). The results of the research in the first cycle of principal observation (3.80), average teacher observation (3.33) and the results of academic supervision in grade average score (63.67). In the second cycle of principal observation on average (4.40) with percentage of achievement (100%), average teacher observation (4.33) with percentage of achievement (100%) and academic supervision result in grade average grade (81.22) with the percentage of achievement (100%). The success indicator has been reached, the research stated successful and stopped in cycle II. The result of the research on the 2nd cycle showed the improvement of the classroom teacher's competence in the actual learning process in the classroom. It is recommended that other principals conduct similar research in an effort to improve the competence of teachers, and to other classroom teachers to carry out the learning process in accordance with well-planned scenarios and responsibly for the improvement of learning achievement of learners under responsibility.